Towards the creation of a “collective conscience” on hygiene and safety at the workplace: occupational medicine and educational action on workers (Spain, 1940-1980) - Martínez-Pérez, José (Historia y Memoria de la Educación, 2021)
The Franco regime expressed its concern about occupational hazards very early on. Accidents at work and occupational diseases were not only a humanitarian problem, but also a threat to production. Occupational med¬icine was thus seen as a discipline that could make an important contribu¬tion to combating the damage caused by inadequate hygiene and a lack of safety in the workplace. This article examines how occupational medicine approached the role of educating workers about the prevention of occupational hazards in the workplace. Taking as a reference the ideas on this issue expressed by Span¬ish occupational medicine specialists in their scientific publications, and the legislative sources in which their approaches were incorporated, the ar-ticle highlights how their contributions were in line with the regime’s objec¬tive of generating, among workers, a “collective conscience” of the need to combat accidents at the workplace and occupational diseases. It also shows how this indoctrination helped to develop the argument that there was a responsibility on the part of the worker for the loss of his or her health.